Barbaloin: A concise report of its pharmacological and analytical aspects - Patel D.K.; Patel K.; Tahilyani V. (My University, 2025)
Barbaloin is C-glucoside of aloe emodin anthrone which is found in the plant name as . Aloe vera is a perennial succulent (Liliaceal), also called the healing plant. Barbaloin have variety of pharmacological activity such as strong inhibitory effect on histamine release, anti-inflammatory, cathartic, antiviral, antimicrobial, anticancer, antioxidant activity and alternative for pharmaceutical or cosmetic applications. The peak amount of barbaloin was reached about 3 h after oral administration. Concentration of barbaloin in . Aloe vera leaves was shown to depend on the leaf part, age, and position of the leaf. Young leaves contain more barbaloin compared to old one. Various researches have been done on barbaloin but still the relationship between the barbaloin and its overall effect has not been clarified. A more specific perceptive of the pharmacological activities of barbaloin is required to develop for pharmaceutical purpose. Many attempts have been made regarding its isolation, biological activity to examine their effects, and clarify their functional mechanism. This review gives a brief idea about its uses, ethnomedicinally and commercially important analytical techniques and their pharmacological activities. © 2012 Asian Pacific Tropical Biomedical Magazine.